Validation of Safety and Efficacy of Real Time Multi Vital Remote Monitoring in Patients with Chronic Ischemic Heart Disease - Patibandla, Sowjanya; Adepu, Rajani; Thamma, Appireddy; Bheemanapally, Madhuri (International Journal of Innovative Research in Medical Science, 2023)
Background: The emerging role of technology in health settings is paving the pathway for novel ways to manage chronic diseases. In recent times, continuous remote monitoring of vital signs using wearable devices has gained immense interest because it enables real-time access to patient data from anywhere. Aim: The objective of this study was to correlate the vital parameters; including ECG, pulse rate, respiratory rate, temperature, heart rate, oxygen saturation, and blood pressure; derived from Real Time Multi vital remote monitoring (RTMVRM) solution and standard vital monitoring methods in chronic ischemic heart disease patients, stable on medication. Methods: A total of 199 patients with confirmed diagnosis of chronic ischemic heart disease, stable on medication, presenting to the Department of General Medicine in ESIC Medical College and Hospital, Hyderabad, were enrolled into the study. The data for Vital parameters was obtained from the subjects at prespecified time points for a 24 hr duration using both RTMVRM and standard methods under direct and continued supervision of the physician. The Spearman’s rank coefficient of correlation was used to evaluate the correlation between the data obtained from RTMVRM solution and standard measurements. The study also examined the safety and efficacy of the RTMVRM using the Vigo Vitals solution. Results: The vital parameters showed statistically significant (p<.0001) positive correlations (spearman) between the RTMVRM solution and standard measurements for pulse rate (0.9418), respiratory rate (0.96766), temperature (0.82103), heart rate (0.98522), systolic BP (0.97468), diastolic BP (0.90832) and SpO2 (0.99620) at 24th hour. The ECG data showed statistically significant (p<.0001) positive correlations (spearman) between the RTMVRM solution and standard measurements for P-wave 0.94749, PR-interval 0.93432, QRS-complex 0.95305, RR-interval 0.66011, QT-interval 0.77310, ST-segment 0.97749 and T-wave 0.95881 at 24th hour. Vigo vitals solutions reported 99% accuracy with 99% sensitivity and 100% capture rate. No device related serious adverse events were reported during the study. Conclusion: The results of this study validated the remote monitoring technology of RTMVRM, a cloud technology based vital monitoring solution. With its ability to offer access to continuous vitals in real time, RTMVRM may enable quick clinical decisions, prevent complications, and enable care providers to stay ahead of the disease. Both the clinician and the patient’s satisfaction were guaranteed by the solution, with accuracy and precision in vital monitoring and a decluttered monitoring experience.